The Solo Sarathi Samchan for Clarinet by Lieutenant Colonel Wichit Hothai (National Artist) - Bhantumkomol, Kasemsun; Nakrob, Saran (Rangsit Music Journal, 2021)
The purposes of this research are 1) To study the biography and works of Lieutenant Colonel Wichit Hothai (National Artist), and 2) To analyze The Solo Sarathi Samchan for Clarinet by Lieutenant Colonel Wichit Hothai (National Artist). The results clision of the research were: 1) Lieutenant Colonel Wichit Hothai has a lot of various works in music: performing, composition, teaching, including the other academic services. Due to a number of works caused he’s got promoted to be a National Artist in the year 2012. 2) From an analysis in The Solo Sarathi Samchan for Clarinet by Lieutenant Colonel Wichit Hothai (National Artist), it is found that the Sarathi song is originated since the Ayudhaya period and had been developed from time to time. Today the song is a monophonic texture in ternary form, which has ranged between the highest pitch on F6 and Lowest pitch on A3. The melodic motion is rather conjunct than the disjunct. Most of the ornamentation technique used is the Sabat (appoggiatura) following by the Krathop (acciaccatura) technique. Moreover, it is found the other techniques which are: Uean (pitch bending), Sado (triplet), Note-loi (cadenza), Phansiang (glissando), Ruap (pitch sliding), Lin-phanlom (staccato) and Phrom (trill).